2019
DOI: 10.1002/tox.22884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on osteoclast differentiation during bone injury in female mice

Abstract: Cadmium (Cd) is a toxic heavy metal that represents an occupational hazard and environmental pollutant toxic heavy metal, which can cause osteoporosis following accumulation in the body. The purpose of this study was to investigate the effect of Cd on bone tissue osteoclast differentiation in vivo. Female BALB/c mice were randomly divided into three groups and given drinking water with various concentrations of Cd (0, 5, and 25 mg/L) for 16 weeks, after which the mice were sacrificed after collecting urine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
1
30
1
3
Order By: Relevance
“…In this process, Cd was more cytotoxic [ 20 ]. In addition, compared to male animals, females were more susceptible to Cd in bone [ 21 , 22 ]. One possible explanation is that Cd exposure can reduce the level of estrogen 2, which inhibits the osteoclast activity and reduce bone absorption [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this process, Cd was more cytotoxic [ 20 ]. In addition, compared to male animals, females were more susceptible to Cd in bone [ 21 , 22 ]. One possible explanation is that Cd exposure can reduce the level of estrogen 2, which inhibits the osteoclast activity and reduce bone absorption [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium is a serious environmental heavy metal pollutant, which has a half-life of 10-30 years, is widely deposited in the stomachs, intestines, livers, pancreases, testes, ovaries, bone marrow, lungs, muscles and fats of humans and animals, and induces apoptosis and autophagy (37,38). Studies on Cd toxicity in bone tissue have shown that Cd turns mesenchymal stem cells from osteogenic differentiation to adipogenic differentiation, and promotes the generation of osteoclasts with bone resorption, thereby affecting bone homeostasis and reducing long bone density and calcium content (39)(40)(41). Kalisińska et al showed that the content of Cd in cartilage tissue is higher than in bones and interferes with the absorption of copper, zinc, iron, manganese, and other trace elements in cartilage, thus causing osteoarthritis and osteoporosis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced ratio of OPG and RANKL via altered expression of IL-1, IL-17 and TGF- [72] Inhibited expression of RUNX2, OSX, OPN, OCN and COL1A2 by suppressing the Wnt/ -catenin pathway [ 72,74] Induction of osteoblast apoptosis Cytoskeleton disruption owing to actin depolymerization [75] DNA fragmentation probably by inducing ROS [76] Oxidative stress via activation of p38 MAPK pathway and inhibition of Erk1/2 pathway [77] Enhanced osteoclast differentiation Increased ratio of RANKL/OPG and TRAP activity [ 67,78] Increased levels of IL-6 and IL-8 in osteoblasts via TLR4 activation [78] Inhibited formation and enhanced degradation of extracellular bone matrix Induction of MMP1, MMP3, MMP9 and MMP13, and decreased synthesis of collagen 1, GAGs and PGs via inflammatory response (IL-1 and IL-6) and ROS production [ 78,81] Disturbed Ca and P homeostasis and inhibited mineralization…”
Section: Inhibited Osteoblast Differentiationmentioning
confidence: 99%